DISKRIMINASI TERHADAP NILAI FEMINIMISME DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Teguh Alfaidzin; Ida Ayu Made Wedasuwari; I Gusti Ayu Putu Tuti Indrawati (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
The purpose of this research is: (1) to find out the forms of discrimination and (2) to know the value of feminism in the novel